Strategi Bersaing dengan Agile Manufacturing - Hamidah Tussifah (University of Darussalam Gontor, 2017)
Competitive advantage now increasingly rests upon a dynamic capability to compete successfully in an environment of frequent, challenging and unpredictable change. The agile manufacturing a recently popularized concept has been advocated as the 21st century manufacturing paradigm. In adopting and developing the key elements of agile manufactruring, there is requirement for enterprises to overcome the philosophical challenges of a shift from mass/lean production to the customization of agility. Beside that, enterprises should explore the key success factors to support succesfull agile implementation.